Competitive Advantage in the Business Environment: The Role of Innovation and Knowledge Management in Sago-Processing MSMEs in the Meranti Islands Regency - Arrisky, Freshly; Samsir; Siregar, Prima Andreas (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
This study discusses the role of innovation and knowledge management in achieving competitive advantage for sago-processing MSMEs in the Meranti Islands Regency. The sample consisted of 95 sago-processing MSMEs located in the Meranti Islands Regency. This study argues that innovation is essential for product development and differentiation, whereas knowledge management is crucial for the creation, validation, presentation, distribution, and application of knowledge. This study also highlights the importance of dynamic capabilities in enhancing competitiveness and achieving a competitive advantage in the business environment. The study found that sago-processing MSMEs in the Meranti Islands Regency face challenges in adapting to changes in the business environment because of the absence of innovation in their products and insufficient knowledge management. The study concluded by emphasizing the need for sago-processing MSMEs to adopt innovation and knowledge management strategies to achieve a competitive advantage in the market